The Swear Words Used by Gordon Ramsay in Hell's Kitchen Episode of Sushi Showdown - Kristina Tedja; Jusuf Imam Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study analyzes the swear words used by Gordon Ramsay in the Hell’s Kitchen episode titled Sushi Showdown. Using Battistella’s (2005) theory, this research identifies the types of swear words he uses, including epithets, profanity, vulgarity, and obscenity. The data were taken from Gordon Ramsay’s utterances during the cooking challenge in the episode and analyzed using a qualitative approach. This study also counts how many times each type of swear word appears. The research found that Gordon Ramsay used all types of swear words: Epithets, Profanity, Vulgarity, and Obscenity. However, the highest frequency is obscenity, such as fuck you, fuck me, fuck off. This “fuck” word is very common in English and is quite often used in daily interactions. In conclusion, Gordon Ramsay’s use of swear words in Sushi Showdown reflects his communication style in managing stress and authority in a professional kitchen. Rather than serving purely as insults, the swear words function to highlight mistakes, push performance, and maintain control during service. This research can be useful for students and future researchers who are interested in language use, swearing, and communication in TV shows.